Investigating Digital Citizenship Literacy Skills: Development of Perceived Knowledge of Students at Postgraduate Level - Yasar, Riffat (IJLTP, 2025)
The ability to effectively navigate the digital world and promote responsible digital citizenship among distance learners is crucial for educators. Digital citizenship refers to standards of behavior when using technology. Present study was conducted to investigate the perceived knowledge of postgraduate students on digital citizenship literacy. The study was quantitative in nature which used survey method. The study was based on the digital citizenship framework of Ribble and Park (2022). The tool was developed under three scales of this framework a) collaboration with others, b) respect for oneself and others, and c) keeping themselves and others safe. Under these three scales, there were nine dimensions of digital citizenship literacy. Population comprised of postgraduate students who were studying at Allama Iqbal Open University in district Muzaffarabad AJK. The sample of this research study was 370 which was drawn using random sampling technique. Major findings of the study revealed that students had good perceived knowledge of digital citizenship literacy in all three scales of Ribble’s framework (perceived knowledge in collaboration-related areas, including digital literacy, ICT skills, communication, and online commerce). Respondents demonstrated adequate awareness of keeping themselves and others safe, especially in digital health, safety practices, and online security measures. It is concluded that study revealed that postgraduate students had ample amount of awareness on digital citizenship literacy (etiquette, law, online commerce, and communication, digital health, safety, security practices etc.). Based upon results of relatively low mean score in perceived knowledge in digital access and literacy dimensions, it’s recommended to deliver targeted educational interventions by stakeholders of digital learning environments.